Characterisation of regenerants obtained under selective conditions after Agrobacterium-mediated transformation of citrus explants reveals production of silenced and chimeric plants at unexpected high frequencies - Domínguez, Alfons; Cervera, Magdalena; Perez, Rosa; Romero, Juan; Fagoaga, Carmen; Cubero, Jaime; López, María M.; Juárez, José; Navarro, Luis; Pena, Leandro (2017)
Genetic transformation has been achieved for several citrus genotypes. However, regeneration of escapes at high frequency is a major problem, making the available procedures rather inefficient. Attempts to improve selection by increasing the concentration of kanamycin, used as the selective agent, or substituting it by geneticin have been unsuccessful. Here, we have critically assessed the actual frequency and origin of escapes in citrus by using visual screening with beta-glucuronidase (gusA) and green fluorescent protein (gfp) markers, by studying the persistence of engineered Agrobacterium in the explants, and by characterising through Southern blot analysis all the regenerants obtained under kanamycin selection. Our results show that inefficient selection could be attributed to the protection of the non-transformed cells from the selective agent by the surrounding transformed cells, and to the persistence of kanamycin-resistance Agrobacterium in explant tissues over long periods of time after co-cultivation. This also explained the high frequency (12%) of chimeric shoots that were commonly recovered. High frequency regeneration of chimeras that resulted from the fusion of different transformation events is reported for the first time. On the other hand, molecular analysis of all the regenerants reveals that transformation frequency is underestimated when based on the expression of a screenable marker gene, and that low expressors and silenced lines could account for at least 25% of those plants considered escapes based on selectable and screenable marker analysis. Consequences of these results at the practical level are also discussed.